2017
DOI: 10.1007/s00041-017-9534-x
|View full text |Cite
|
Sign up to set email alerts
|

A Theory of Super-Resolution from Short-Time Fourier Transform Measurements

Abstract: While spike trains are obviously not band-limited, the theory of super-resolution tells us that perfect recovery of unknown spike locations and weights from low-pass Fourier transform measurements is possible provided that the minimum spacing, ∆, between spikes is not too small. Specifically, for a measurement cutoff frequency of f c , Donoho [2] showed that exact recovery is possible if the spikes (on R) lie on a lattice and ∆ > 1/f c , but does not specify a corresponding recovery method. Candès and Fernande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Note that both aforementioned works [6,18] are formulated in terms of off-grid spikes. Another article about off-grid spikes was [1] by Aubel et al, who also arrived at MSF > 1 if windowed Fourier (or short-time Fourier transform) measurements are available. Furthermore, there are two works that do not require MS. De Castro and Gamboa [10] showed that K spikes can be resolved from 2K +1 Fourier samples; and with additional positive assumption of point sources, Donoho et al [14] showed that 2K noiseless measurements are sufficient to yield exact recovery of K positive spikes.…”
Section: Definition 1 (Minimum Separation)mentioning
confidence: 96%
“…Note that both aforementioned works [6,18] are formulated in terms of off-grid spikes. Another article about off-grid spikes was [1] by Aubel et al, who also arrived at MSF > 1 if windowed Fourier (or short-time Fourier transform) measurements are available. Furthermore, there are two works that do not require MS. De Castro and Gamboa [10] showed that K spikes can be resolved from 2K +1 Fourier samples; and with additional positive assumption of point sources, Donoho et al [14] showed that 2K noiseless measurements are sufficient to yield exact recovery of K positive spikes.…”
Section: Definition 1 (Minimum Separation)mentioning
confidence: 96%
“…A similar statement continues to hold when only a random subset of the uniformly spaced samples are available [Tan+13]. Related convex programs have been studied for denoising [BTR13], signal recovery from short-time Fourier measurements [ASB15], deducing time-frequency components of a signal with applications in super-resolution radar [HMS16], and line spectral estimation from multiple measurements [LC16].…”
Section: Introductionmentioning
confidence: 98%
“…It converts the time-domain signals into two dimensional TFD, which presents a frequency variation trend with time. Recently, many studies about STFT were conducted, getting good results [ 32 , 33 , 34 , 35 ]. In [ 32 ], Aubel developed a theory of super-resolution from STFT measurements and presented a new recovery method for pure Fourier measurements.…”
Section: The Proposed Recognition Methods Analysismentioning
confidence: 99%